Production offshoring and the skill composition of Italian manufacturing firms: A quasi-experimental analysis - Roberto Antonietti; Davide Antonioli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
This work explores the effects of production offshoring on the workforce skill composition of manufacturing firms. Its aim is to assess if the firms' strategy to offshore production activities determines a bias in the in-house employment of labor in favour of high-skilled workers. Using three repeated cross-sections of firm-level data over the period 1995-2003, we employ a nonparametric analysis based on propensity score matching thanks to which we can control for selectivity bias without relying on a specific functional form of the relations of interest. We test the effect of production offshoring on the workforce skill composition of manufacturing firms by employing different measures of skills by occupational title. Our results point to a weak, but down-skilling, impact of delocalization on the labor composition of Italian manufacturing: in particular, we find that firms that farmed out production activities in 1998-2000 generally employ a lower share of skilled, non manual, workers with respect to the counterfactual of nondelocalizing firms. These results seem to be in line with an idea of defensive offshoring. However, despite the usual findings that mainly stress the negative impact of delocalization on low-skilled workers, we find here that middle-managers category is the most affected. Such evidence may find a twofold explanation: on the one hand, skilled workers can decline more than unskilled workers because of a substitution effect that is driven by the will of reducing not only redundant activities, but also intermediate skills-intensive activities as control and coordination for which middlemanagers are employed for. On the other hand, skilled workers may decline in absolute terms, because of a quantity effect that occurs when firms decide to transfer managerial staff in order to coordinate and supervise the activities shifted abroad.
Keywords: 330